2022
DOI: 10.7554/elife.82050
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2-specific CD4+ and CD8+ T cell responses can originate from cross-reactive CMV-specific T cells

Abstract: Detection of SARS-coronavirus-2 (SARS-CoV-2) specific CD4+ and CD8+ T cells in SARS-CoV-2-unexposed donors has been explained by the presence of T cells primed by other coronaviruses. However, based on the relative high frequency and prevalence of cross-reactive T cells, we hypothesized CMV may induce these cross-reactive T cells. Stimulation of pre-pandemic cryo-preserved PBMCs with SARS-CoV-2 peptides revealed that frequencies of SARS-CoV-2-specific T cells were higher in CMV-seropositive donors. Characteriz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 74 publications
2
9
1
Order By: Relevance
“…Cross-reactive clusters of differentiation 4+ and clusters of differentiation 8+ T-cell responses to SARS-CoV-2 were documented in 90% of prepandemic samples from Uganda [25] , but only 10-50% in prepandemic samples from the USA or Europe [26] , [27] , [28] . Cross-reactive T-cell responses may derive from both homologous pathogens (other coronaviruses, including the four globally-distributed coronaviruses or other coronaviruses with country distribution largely overlapping with malaria burden [20] ) and non-homologous ones (e.g., cytomegalovirus) [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Cross-reactive clusters of differentiation 4+ and clusters of differentiation 8+ T-cell responses to SARS-CoV-2 were documented in 90% of prepandemic samples from Uganda [25] , but only 10-50% in prepandemic samples from the USA or Europe [26] , [27] , [28] . Cross-reactive T-cell responses may derive from both homologous pathogens (other coronaviruses, including the four globally-distributed coronaviruses or other coronaviruses with country distribution largely overlapping with malaria burden [20] ) and non-homologous ones (e.g., cytomegalovirus) [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Bacher and colleagues demonstrated that in previously SARS-CoV-2-unexposed individuals with COVID-19, pre-existing SARS-CoV-2-reactive circulating T cells possessed low TCR avidity and were enriched in patients with more severe disease, arguing against a protective function for cross-reative T cells (49). Furthermore, cross-reactivity might not only be limited to human coronaviruses (46, 49), and others have shown that microbial peptides from commensal bacteria and other viruses are potential sources of heterologous immunity to SARS-CoV-2 (68, 69). Here, we predicted that TCRs specific for immunodominant SARS-CoV-2 peptides in our dataset cross-react with other human coronaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 0.23% of the CD3 + TCR + population in PB was contained in putative MHC class II-restricted CDR3α or CDR3β virus-reactive CD4 + T cells. Since there were no matches to a CDR3α/β pair from the VDJdb, some of these TCR may not be specific for the same published viral epitope and may cross-react with other viruses 62 . Due to the paired study design, in both PB and ST of donor 4 we identified a clonotype matching a known CMV-reactive CDR3β, which we validated by tetramer staining in PB.…”
Section: Discussionmentioning
confidence: 99%